(untitled) (Journal of Oriental Studies, 2022)
The written heritage of the Kipchak language includes historical, literary and linguistic monuments written in the Mamluk-Kipchak language with Arabic graphics, and the latter includes Turkish-Arabic dictionaries and grammatical works. These works, written by the Mamluk Turks, who ruled Egypt at that time, in order to teach the local Arab people the Kipchak language, provide us valuable information not only on the language but also on the culture of the Kazakh people, containing valuable data in Arabic and Kipchak. There are six main Mamluk-Kipchak dictionaries: “Kitab al-idrak li-lisan al-atrak”, “Kitab attuhfa az-zakiya fi al-luga at-turkiya”, “al-Qawanin al-kulliyya lidabt al-lughat-turkiya”, “Kitab ad-durrat al-mudiya fi al-lugat at-turkiya ala at-tamam wa al-kamal”, “Kitab majmua tarjuman turki wa ajami wa muguli wa farsi” and “Kitab bulgat al -mushtaq wa fi lugat at-turk wa al-kifjaq”. Since the subject of nature and its phenomena are covered in several dictionaries, in this study we will consider words related to it that are common or different from each other. The purpose of the work is to study the vocabulary in the field of “nature” in dictionaries written in the Mamluk-Kipchak language; distinguish lexical units of working nature from dictionaries; comparison of Arabic and Mamluk-Kipchak equivalents; identify similarities and differences in Mamluk-Kipchak dictionaries; and provide equivalents in modern Turkish, Kazakh, and English. The methodology of the study includes such stages as distinguishing lexical units in manuscripts, copying from the manuscript version on a computer page, finding equivalents in Turkic languages. Key words: Mamluk-Kipchak, Arabic, vocabulary, manuscript, dictionary.